2018
DOI: 10.1186/s40069-018-0239-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Age-related Changes in the Relative Permittivity of Concrete Bridge Decks on Korea Expressways

Abstract: The purposes of this study were to investigate the seasonal variations in the relative permittivity of actual concrete bridge decks of various ages on Korea expressways, and to propose a practical way to calibrate two critical effects, to assess the condition of the concrete bridge decks with better accuracy. For these purposes, fifty-three actual concrete bridge decks on Korea expressways were scanned using an air-coupled ground penetrating radar (GPR) system, and the relative permittivity of the concrete was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In other words, as the age increased, the dielectric constant decreased at a reduced rate. This trend followed the behavior observed in the equation for bare concrete bridge deck [20]. In this study, an approximate formula representing the relationship between the dielectric constant of concrete deck with asphalt overlay and concrete age (service period of bridges) was established using nonlinear regression analysis, ε Age r,c = −1.08 ln(Age conc ) + 11.41 (8) where Age conc is the concrete age at the time of GPR measurements (year).…”
Section: Influence Of Concrete Age and Relative Humidity Of Airsupporting
confidence: 53%
See 3 more Smart Citations
“…In other words, as the age increased, the dielectric constant decreased at a reduced rate. This trend followed the behavior observed in the equation for bare concrete bridge deck [20]. In this study, an approximate formula representing the relationship between the dielectric constant of concrete deck with asphalt overlay and concrete age (service period of bridges) was established using nonlinear regression analysis, ε Age r,c = −1.08 ln(Age conc ) + 11.41 (8) where Age conc is the concrete age at the time of GPR measurements (year).…”
Section: Influence Of Concrete Age and Relative Humidity Of Airsupporting
confidence: 53%
“…In general, the GPR survey data appears to be greatly dispersed, which is mainly due to the variability of bridge components (e.g., concrete age, degree of deterioration, water content, etc.). However, it could be observed that the higher values of relative permittivity are shown in relatively new concrete bridges (0-10 years), which was also observed in concrete bridge decks without asphalt overlay [20]. Young concrete has plenty of water in the concrete pore system, leading to higher dielectric constant than the values in mature concrete in old bridges.…”
Section: Methods Of Survey and Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…Using the sparse and smooth reflectivity R obtained from the above iterative process, the transmitted wavelet W can be estimated based on (9). This is done in a similar way to the derivation of the Wiener filter.…”
Section: B Split Bregman Algorithmmentioning
confidence: 99%